Phase field simulations of microstructure evolution of monocrystalline and polycrystalline silicon by forced convection - Zhang, Dianxi; Yang, Xiufan; Qin, Xinmao; Wang, Huaizhi; Song, Qingjiang (Transactions on Engineering and Technology Research, 2024)
In this study, the phase field method was used to numerically simulate single crystal and polycrystalline silicon under the action of forced convection. Following the construction of the phase field model, the effects of parameters such as the degree of undercooling and convection velocity on the growth morphology of monocrystalline and polycrystalline silicon were simulated. The crystal nuclei of different sizes and multi-grain growth conditions of different nucleation times were obtained. The results showed that the growth rate of the upstream tip was the fastest, followed by that of the horizontal direction, and the growth rate of the lower end was the slowest under forced convection. When the undercooling degree was small, anisotropy was not obvious, and grain growth was slow. When the undercooling degree was greater than 0.65, the interface became unstable, and side branches appeared in the direction of the horizontal dendrite arm, while growth was transformed from the non-small crystal plane to the small crystal plane. Under the action of forced convection, the larger the flow velocity, the faster the crystal growth, and the faster the growth speed in the upstream direction of the grain. During the early growth stage, the overall growth rate of the larger initial nuclei was slower than that of the smaller initial nuclei, and subsequently, the difference was not significant. As the grains continued to grow, the thermal diffusion layers of the adjacent grains were in contact with each other, resulting in competitive growth.